2004
DOI: 10.4049/jimmunol.172.12.7385
|View full text |Cite
|
Sign up to set email alerts
|

KIR2DL5 Can Inhibit Human NK Cell Activation Via Recruitment of Src Homology Region 2-Containing Protein Tyrosine Phosphatase-2 (SHP-2)

Abstract: Human NK cells use class I MHC-binding inhibitory receptors, such as the killer cell Ig-like receptor (KIR) family, to discriminate between normal and abnormal cells. Some tumors and virus-infected cells down-regulate class I MHC and thereby become targets of NK cells. Substantial evidence indicates that the mechanism of KIR-mediated inhibition involves recruitment of the protein tyrosine phosphatases, Src homology 2-containing protein tyrosine phosphatase-1 (SHP-1) and SHP-2, to two phosphorylated cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
47
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 56 publications
6
47
0
Order By: Relevance
“…We have also shown that KIR2DL5 cross-linking is capable of inhibiting the NK cell cytotoxicity against a xenogeneic FcR ϩ target cell, an ability that likely involves the recruitment of the SHP-1 and SHP-2 phosphatases. The inhibitory effect and the binding of both phosphatases to KIR2DL5 in cells expressing naturally the receptor are in agreement with previous predictions based on the KIR2DL5 primary structure (23) and on the behavior of NK-92 cells transduced with FLAG-tagged-or chimerical molecules containing the KIR2DL5 cytoplasmic tail (38). The higher proportion of SHP-2 bound by KIR2DL5 in comparison with KIR2DL1 we have observed here (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We have also shown that KIR2DL5 cross-linking is capable of inhibiting the NK cell cytotoxicity against a xenogeneic FcR ϩ target cell, an ability that likely involves the recruitment of the SHP-1 and SHP-2 phosphatases. The inhibitory effect and the binding of both phosphatases to KIR2DL5 in cells expressing naturally the receptor are in agreement with previous predictions based on the KIR2DL5 primary structure (23) and on the behavior of NK-92 cells transduced with FLAG-tagged-or chimerical molecules containing the KIR2DL5 cytoplasmic tail (38). The higher proportion of SHP-2 bound by KIR2DL5 in comparison with KIR2DL1 we have observed here (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…KIR2DL5 has alleles with mRNA transcripts that are clonally distributed in NK and T lymphocytes and ones that are apparently not transcribed, the most common of which are, respectively, KIR2DL5A*001 and KIR2DL5B*002 (23,27). Finally, KIR2DL5 is predicted to encode a purely inhibitory receptor, according to its signaling motifs (two ITIMs, the second one having a noncanonical TxYxxL sequence, and a transmembrane region lacking charged amino acid residues) and to the behavior of cells transfected with tagged or chimerical KIR2DL5 constructs (23,38).…”
mentioning
confidence: 99%
“…Consistent with this, we found that in transfected cells Ly49B does indeed associate with SHP-1 in a phosphorylationdependent manner. Ly49B also interacted with SHP-2, a protein tyrosine phosphatase that can associate with other Ly49 receptors (13,49,50) and forms an inhibitory complex with killer Ig-related receptors (51). It was also found to associate with SHIP-1, a phosphatase that is thought to play a major role in negative intracellular signaling via its degradation of phosphatidylinositol 3,4,5-trisphosphate.…”
Section: Discussionmentioning
confidence: 91%
“…4 Despite clustering together into a discrete lineage with high structural homologies, the KIR2DL5 and 2DL4 differ substantially in their amino-acid sequences, genomic locations, population distributions, level of transcriptions, cellsurface expressions, ligand specificities and signaling functions. [5][6][7][8][9] The KIR2DL4 gene is present on most KIR haplotypes and occurs at a frequency of 100% in most populations, whereas KIR2DL5 is variable among KIR haplotypes and thus differs considerably between populations in its frequency. [10][11][12] Two copies of the KIR2DL5 genes have been characterized, KIR2DL5A and KIR2DL5B, that show 99.5-99.7% identity in their coding sequences.…”
Section: Introductionmentioning
confidence: 99%
“…8,15 Although KIR2DL4 has been implicated in both inhibitory and activating functions, 6,[16][17][18] KIR2DL5 appears to be solely an inhibitory receptor. 7 Multiple sequences for both KIR2DL5A and KIR2DL5B loci have been characterized from individuals of different ethnic origins. 13 However, the nature of KIR2DL5 sequence polymorphism within distinct ethnic populations is not known.…”
Section: Introductionmentioning
confidence: 99%